Increase of data protection level for visual information in control systems - Bushma, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Formalized description of data transmission between technical means and an
operator from the viewpoint of information security is presented. The most widely used
symbolic and bar graph data representation forms are analyzed and compared. An
analytical estimation of redundancy inherent to the considered information models is
offered.